The effect of solution treatment under loading on the microstructure and phase transformation behavior of porous NiTi shape memory alloy fabricated by SHS - Kaya, Mehmet; Orhan, Nuri; Kurt, Bulent; Khan, Tahir I. (Elsevier Science Sa, 2009)
Porous NiTi shape memory alloy (SMA) was fabricated by self-propagating high-temperature synthesis (SHS). With this study, a new solution treatment solution treatment under loading was applied to porous NiTi SMA fabricated by SHS to determine microstructural improvement regarding single phase NiTi. The effect of solution treatment under load on chemical composition, constituent phases and phase transformation behaviors of the specimens was investigated and discussed. The chemical composition of the specimens considerably changed with solution treatment under loading. Intermetallic phases such as Ti2Ni and Ni4Ti3 disappeared, the density of B2(NiTi) phase increased and phase transformation temperatures sharply decreased. Porous single phase B2(NiTi) SMA with high chemical homogeneity could be obtained by the load applied during solution treatment at 1050 degrees C. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: NiTi shape memory alloy; Porous materials; Self-propagating high-temperature synthesis; Phase transformation behaviors